Motivación y logros de aprendizaje del área de desarrollo personal ciudadanía y cívica en estudiantes de educación secundaria institución educativa Nº 60087 Lucille Gagne Pellerin Santa Clotilde, Río Napo 2023 - Chavez Rengifo, Fiorela Zoilita (2024)
The main objective of this study was to determine the relationship between the level of motivation and learning achievements in Personal Development, Citizenship and Civic in Secondary Education students of the educational institution No. 60087 Lucille Gagne Pellerin, Santa Clotilde rio Napo 2023. A quantitative approach of a correlation type was adopted, using a specific cross sectional correlation design. The sample consisted of 104 students selected from a population of 141. A questionnaire was used as a tool to collect data on the study variables. The main results indicated a very strong correlation between the level of motivation and academic performance in the area. This confirmed the research hypothesis, demonstrating that the motivation is significantly related to the learning achievements in Personal Development, Citizenship and Civic in Secondary Education students in the institution.